2020
DOI: 10.1002/qre.2733
|View full text |Cite
|
Sign up to set email alerts
|

An enhanced approach for the progressive mean control charts: A discussion and comparative analysis

Abstract: Recently, a new double progressive mean (DPM) control chart has been proposed in the literature of statistical process control. In the said proposal, an important term is missing in the variance expression of the DPM statistic that affects the detection ability of the proposed chart. In this study, we have derived and provided the correct version of the said variance along with its corresponding control limits. The run length profiles of the DPM chart are investigated, and the results are updated for the new v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…For normal observations, Abbas et al 47 extended the analysis with the DPM chart, based on a PM of progressive means, which adds even more weight to the older observations (see Section 4). However, Riaz et al 48 found an error and corrected the DPM variance to improve its performance. Focusing on a different problem, Zafar et al 49 proposed a chart to monitor the variance.…”
Section: Pm Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…For normal observations, Abbas et al 47 extended the analysis with the DPM chart, based on a PM of progressive means, which adds even more weight to the older observations (see Section 4). However, Riaz et al 48 found an error and corrected the DPM variance to improve its performance. Focusing on a different problem, Zafar et al 49 proposed a chart to monitor the variance.…”
Section: Pm Approachmentioning
confidence: 99%
“…Now, we want to compare the weights of the PM chart, the DPM chart introduced in Riaz et al, 48 and the HWMA chart with the weights of the EWMA chart, the DEWMA chart from Shamma et al 74 and more recently in Zhang et al, 75 and the TEWMA chart proposed in Alevizakos et al 76 . Next we provide illustrations for t=2,5,10, and 100.…”
Section: Weighting Patternsmentioning
confidence: 99%
“…Subsequently, Abbas et al 45 suggested double progressive mean (DPM) control charts revamp the effectiveness of the PM chart. Further, a refined version of the DPM chart was discussed by Riaz et al 49 So, we evolved model based PM and DPM structures to supervise minor to moderate shifts in process location, which are explained in the following sections.…”
Section: Proposed Poisson Model-based Schemesmentioning
confidence: 99%
“…In literature, several researchers discovered that DPM structure has excellent identification power as compared to PM structure. [45][46][47][48][49][50] Furthermore, we have assessed the recommended techniques with respect to run length properties and contrasted them with existing SR-EWMA chart. Also, the proposed structures are executed on the number of 3D defective products in an additive manufacturing process.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, Var(PDPMt) provided in (3) is not correct and we derive its correct version. The correct variance of the PDPMt statistic following Riaz et al 9 is derived as follows:…”
Section: Derivation Of the Variance Of Double Progressive Mean Statisticmentioning
confidence: 99%